The Analysis of Errors Made by Iraqi Students in Writing (Journal of the College of Languages (JCL), 2006)
Writing plays an effective role in developing one's thinking andenhancing Learning. It is, in fact, a means of widening one's own views aboutthe world for the numerous uses that it can serve (Samuel, 1988:28).In regard to the unquestionable significance of writing in the teaching –Learning process, the traditional approach seems to be far from being able toput such significance into practice. Traditionalists give priority to formulatingstudents' ideas before using prescribed rhetorical framework and thensubmitting the written product for grading. Emphasis is, therefore, limited to theprewriting stage where a certain topic is explored, and the role of the teacher isconfined to assigning the topic and correcting the final version of student'swriting (ibid.).Writing composition is one of the many skills that the student shoulddevelop when Learning a foreign Language. Moreover, it is the mostcomplicated one, since all the other skills from punctuation to the organizing ofthe content of writing interact when writing takes place.